The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4014/jmb.1106.06027
|View full text |Cite
|
Sign up to set email alerts
|

Wild Ginseng Attenuates Anxiety- and Depression-Like Behaviors During Morphine Withdrawal

Abstract: The purpose of this study was to evaluate whether wild ginseng (WG) administration could attenuate anxiety-and depression-like behaviors and expression of corticotrophinreleasing factor (CRF) and neuropeptide Y (NPY) following withdrawal from repeated morphine administration in rats. Male rats were administered daily doses of WG (50, 100, or 200 mg/kg, i.p.) for 5 days, 30 min before morphine injection (40 mg/kg, s.c). The anxiety-and depression-like behavioral responses were measured 72 h after the last morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 23 publications
(30 reference statements)
0
13
0
1
Order By: Relevance
“…Ginsenosides (i.p and p.o.) at a range of doses have also been shown to improve memory and learning impairment in models using morphine or ethanol to create deficits; taken together, these data suggest there may be multiple targets for the effects of ginsenosides on learning and memory.…”
Section: Resultsmentioning
confidence: 88%
“…Ginsenosides (i.p and p.o.) at a range of doses have also been shown to improve memory and learning impairment in models using morphine or ethanol to create deficits; taken together, these data suggest there may be multiple targets for the effects of ginsenosides on learning and memory.…”
Section: Resultsmentioning
confidence: 88%
“…In addition, morphine withdrawal-induced anxiety and depression-like behavior were effectively inhibited by wild ginseng extracts by modulating hypothalamic expression of CRF and NPY [133]. Moreover, the same group of researchers have reported that wild ginseng extracts effectively attenuated morphine withdrawal-induced behavioral sensitization along with modulation of c-Fos expression in nucleus accumbens and TH expression in ventral tegmental area suggesting the possible involvement of ginseng in the modulation of dopaminergic nervous system activity during morphine withdrawal [152].…”
Section: Addictionmentioning
confidence: 93%
“…Interestingly, the antidepressant-like activity was comparable to that of fluoxetine and S111 increased monoamine neurotransmitters in the brain and showed modest inhibitory effects against neurotransmitter reuptake in vitro . In contrast to fluoxetine, S111 inhibited oxidative stress and reduced serum corticosterone level in olfactory bulbectomized animals suggesting S111 modulates depression-like behavior by regulating multiple targets including both central and peripheral inflammation, regulation of hypothalamic corticotrophin-releasing factor (CRF) and Neuropeptide Y (NPY) expression and regulation of glucocorticoid receptor and BDNF expression as well as neurofilament-L in hippocampus [133-135,139]. Many of these results suggest that ginseng and ginsenosides regulate brain neurotransmitter turnover and hypothalamic- pituitary-adrenal axis.…”
Section: Depressionmentioning
confidence: 99%
“…Many studies have demonstrated that morphine withdrawal causes depression- and anxiety-related disorders in humans and corresponding behavioral responses in animals [3,4]. Importantly, depression and anxiety that occur during morphine abstinence often lead to relapse to morphine use in humans [5]. Over the past several decades, several antidepressant classes [i.e., monoamine oxidase inhibitors, selective serotonin reuptake inhibitors (SSRIs), and tricyclic antidepressants (TCAs)] have been developed and clinically used to treat psychiatric side-effects, including depression and anxiety, following morphine withdrawal [2].…”
Section: Introductionmentioning
confidence: 99%